The Role of Cultural Orientation in Adolescent Identity Formation: Self-Construal as a Mediator. - Muttaqin, Darmawan (UI Scholars Hub, 2020)
Cultural context has become one of the key factors in identity formation. Differences in cultural orientation cause differences in self-construal which influence identity formation. This research examined the role of self-construal as a mediator of the role cultural orientation in identity formation. This study recruited 569 participants aged 18-21 years old. The Utrecht-Management of Identity Commitments Scale, Culture Orientation Scale, and Self-Construal Scale were used to measure identity formation, cultural orientation, and self-construal. The results indicated that interdependent self-construal could mediate the role cultural orientation in identity formation and that significant others are important in identity formation.